Perception of medical students about the virtualization of general pathology and special pathology courses - Quispe Mori, Wanda (2022)
Objective. Describe the virtualization process of general and special pathology courses and the perception of students. Methods. Non-experimental, prospective, and cross-sectional study. For the virtual teaching of the courses, the Moodle platform was used; and, for histopathology practices, the Pathpresenter platform was used. 126 students from the general pathology course and 133 from special pathology participated. The questionnaire developed by Justin Krawiec and Quality Matters for Higher Education Rubric was used, consisting of 27 questions with Likert scale responses ranging from 1 to 5, where 1 is valued as totally disagree and 5 as totally agree. It has a reliability of 0.96 according to Cronbach’s alpha coefficient. The global assessments were established using percentiles. Results. Use of Moodle: the clarity of the content obtained an evaluation of 3.9 and 4, while the presence of problems accessing Moodle, obtained an average evaluation of 2.4 and 3. In the dimension classes and evaluation, the usefulness of the virtual practices obtained an average valuation of 3.8 and 3.5. Regarding the third dimension, experience in microscopy virtualization, the statement, “Pathpresenter platform is easy to use and effective for the purpose of the courses”, obtained an average rating of 4.1 and 4.2. Conclusion. The students positively value the virtual practices of pathology, the ease of access and the quality of the images. However, they report having technical difficulties in accessing to Moodle platform.